ANALISIS POTENSI EKONOMI SEKTORAL PADA EMPAT KABUPATEN DI PULAU MADURA - Azmi Faiz Nur; Idah Nuraini (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2011)
The purpose of this research is to determine the pattern of the economy, the advanced sector/subsector on each district, and determining the growth center on the Madura Island. The analysis tools that are used in this research are Typology Klassen, Location Quotient (LQ), and analysis of gravity. The research concluded there are four (4) patterns of economic growth on four districts in the Madura Island. An area that